Contributions to Nearctic Stupkaiella Vaillant (Diptera: Psychodidae) - Curler, Gregory R.; Moulton, John K. (Zootaxa, 2010)
The diagnosis of genus Stupkaiella Vaillant (Diptera: Psychodidae) is revised. Three new eastern Nearctic species, Stupkaiella capricornuata sp. nov., S. lasiostyla sp. nov., and S. robinsoni sp. nov., and the 4th or final instar larva of S. bipunctata Kincaid are described and a key to adult males of the eastern Nearctic species of Stupkaiella is provided.